Examining developmental differences in imagery use with youth soccer players - Gregg, M.; Strachan, L. (Journal of Imagery Research in Sport and Physical Activity, 2015)
Emerging research on youth sport participants has revealed that young athletes use sport-related mental imagery for a variety of purposes such as acquiring sport-specific skills. The present study aimed to replicate previous research regarding developmental differences in imagery use, confirm the utility of the Sport Imagery Questionnaire-Children`s Version (SIQ-C), and clarify the relationship of gender to imagery use in youth sport. Youth soccer players (N = 207) included boys and girls ranging in age from 7 to 16 years. All participants completed the SIQ-C. Results replicated previous research indicating the SIQ-C is a suitable tool for examining imagery use by youth sport participants. Developmental differences similar to previous research were also replicated; younger age cohorts were more likely to use motivational-specific (goal-oriented) images. No gender differences in imagery use materialized; recruiting participants from a single sport allowed direct comparisons between genders and eliminated the confounding variable of sport type.